2020
DOI: 10.3791/60742
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Mosaic Mammary Organoids by Differential Trypsinization

Abstract: The mammary gland is a bilayered structure, comprising outer myoepithelial and inner luminal epithelial cells. Presented is a protocol to prepare organoids using differential trypsinization. This efficient method allows researchers to separately manipulate these two cell types to explore questions concerning their roles in mammary gland form and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…To determine whether ROBO1 promotes alveolar differentiation through its action specifically in one of these cell types, we generated organoids that are mosaic for Robo1 expression ( Fig. 4 A) ( Rubio et al, 2020 ). Robo1−/− basal cells were mixed with Robo1+/+ luminal cells (KO/WT) and, vice versa, Robo1+/+ basal cells were mixed with Robo1−/− luminal cells (WT/KO) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether ROBO1 promotes alveolar differentiation through its action specifically in one of these cell types, we generated organoids that are mosaic for Robo1 expression ( Fig. 4 A) ( Rubio et al, 2020 ). Robo1−/− basal cells were mixed with Robo1+/+ luminal cells (KO/WT) and, vice versa, Robo1+/+ basal cells were mixed with Robo1−/− luminal cells (WT/KO) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Primary cell organoids were grown as previously described ( Rubio et al, 2020 ). Briefly, primary cells were mixed and grown in Matrigel Growth Factor Reduced (GFR), Phenol Red-Free (Corning, CB-40230C) and cultured in basal medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast attachment to substrates is comparatively less robust as opposed to hepatocytes and we exploited this aspect to separate the two cell populations based on differential trypsinization time. The process of differential trypsinization to separate fibroblasts from other cells have been used widely over several years due to the faster trypsinization of fibroblast [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were thoroughly observed under a microscope to ensure that only primary hepatocytes remained attached to the substrates following the first trypsinization step. The process of differential trypsinization to separate fibroblasts from other cells have been used widely over several years due to the faster trypsinization of fibroblast [ 55 , 56 , 57 , 58 , 59 ]. To qualitatively validate the selective trypsinization technique, we replated the trypsinized cell suspension onto collagen-coated TCPS and observed that the cell attached were primarily fibroblasts.…”
Section: Methodsmentioning
confidence: 99%